Multiple‐stressor effects on stream invertebrates: a mesocosm experiment manipulating nutrients, fine sediment and flow velocity. (1st February 2016) - Elbrecht, Vasco; Beermann, Arne J.; Goessler, Gunnar; Neumann, Janis; Tollrian, Ralph; Wagner, Rüdiger; Wlecklik, Andre; Piggott, Jeremy J.; Matthaei, Christoph D.; Leese, Florian
Summary: Land‐use changes have degraded ecosystems worldwide. A particular concern for freshwater biodiversity and ecosystem function are stressors introduced by intensified agriculture. Typically several stressors affect freshwater ecosystems simultaneously. However, the combined effects of these multiple stressors on streams and rivers are still poorly understood, yet of critical importance to improve freshwater management. We investigated responses of benthic macroinvertebrates to three globally important agricultural stressors affecting streams (nutrient enrichment, fine sediment deposition and reduced current velocity), using 64 stream mesocosms (full‐factorial 2 × 2 × 2 design, eight replicates of each treatment combination) established on the banks of the Breitenbach Stream (Hesse, Germany). The experiment ran for 1 month (16 days of colonisation, 14 days of manipulations), and all invertebrates in the mesocosms were collected at the end of this period. Fourteen of the 17 studied invertebrate response variables were affected by one or more stressors each. Negative effects on richness or abundance of pollution‐sensitive Ephemeroptera, Plecoptera and Trichoptera (EPT) taxa were particularly common. Overall, both sediment addition and stream flow velocity reduction had pervasive and strong effects. Responses to sediment addition were mostly negative, whereas decreased current velocity reduced several EPT metrics but increased the abundances of some of the other common taxa. Nutrient enrichment had few effects, but these were consistently negative. Combined stressor effects were mainly additive, with only two interactions found in total, both between reduced velocity and nutrients (on the crustacean Gammarus spp. and ceratopogonid midges). This finding implies that multiple‐stressor responses may be predicted from knowledge of single‐stressor effects in this stream community (unlike the often synergistic or antagonistic responses observed elsewhere). However, further taxon‐specific responses and interactions among stressors may have been obscured by limited taxonomic resolution, especially for the numerically dominant Chironomidae. Genetic approaches are required to address this limitation in the future.